﻿A new Asian lazy toad of the genus Scutiger Theobald, 1868 (Anura, Megophryidae) from southern Tibet, China - Sheng-Chao Shi; Lu-Lu Sui; Shun Ma; Fei-Rong Ji; A-Yi Bu-Dian; Jian-Ping Jiang (ZooKeys, 2023)
In this study, a new species named Scutiger luozhaensis sp. nov. is described from Luozha, southern Tibet, China. Genetic analysis based on two mitochondrial genes 16S rRNA and COI and the nuclear gene RAG1 revealed that the new species belongs to an independent phylogenetic clade close to S. gongshanensis and S. nyingchiensis and shares no RAG1 haplotype with other species. Morphological comparisons based on examined specimens and literatures indicated that it can be diagnosed from congeners by the following combination of characters: (1) body moderate, male body length 47.0–67.2 mm (n = 13), female body length 49.8–66.2 mm (n = 8); (2) maxillary teeth and budding absent; (3) numerous tiny dense nuptial spines present on dorsal surface of fingers I, II and inner surface of finger III of males in breeding condition with similar size; (4) spine patches on belly of males in breeding condition absent; (5) spines on inner surface of forearm and upper arm of males in breeding condition absent; (6) small patches of black spines present near armpit of males in breeding condition absent; (7) adult males without vocal sac; (8) some large warts and tubercles on dorsum gathered into short skin ridges with several spines present on top; (9) space between upper eyelids wider than upper eyelids; (10) spots or irregular cross bands on limbs absent; (11) webbing between toes rudimentary; (12) coloration of dorsal body olive brown to bronze.